(6x+19)-(14x+5)=

Simple and best practice solution for (6x+19)-(14x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x+19)-(14x+5)= equation:


Simplifying
(6x + 19) + -1(14x + 5) = 0

Reorder the terms:
(19 + 6x) + -1(14x + 5) = 0

Remove parenthesis around (19 + 6x)
19 + 6x + -1(14x + 5) = 0

Reorder the terms:
19 + 6x + -1(5 + 14x) = 0
19 + 6x + (5 * -1 + 14x * -1) = 0
19 + 6x + (-5 + -14x) = 0

Reorder the terms:
19 + -5 + 6x + -14x = 0

Combine like terms: 19 + -5 = 14
14 + 6x + -14x = 0

Combine like terms: 6x + -14x = -8x
14 + -8x = 0

Solving
14 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -8x = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -8x = 0 + -14
-8x = 0 + -14

Combine like terms: 0 + -14 = -14
-8x = -14

Divide each side by '-8'.
x = 1.75

Simplifying
x = 1.75

See similar equations:

| .3x=-7 | | 17=4x+1-2x | | -n=30 | | 4x+22=22 | | (6x+14)-(9x+5)= | | 3,75100,000= | | y^2-12y+12=0 | | 13=9x+5-5x | | 2a+6+5a=3a-10 | | -12+.2x-.3x+x=6x | | d^5+5d-4=0 | | 6x^2=x+40 | | 2g-16=-8 | | 5x+12=7x-13 | | y^2-12y+62=0 | | 4-3x=2x-6 | | 4-1(m-2)=12 | | x^3-12x=30 | | x^3-5x=3 | | 14-1(-2p+5)=-2p+9 | | 5(x-4)+2x=4x-1 | | 9m=14fraction | | -2(3k-3)=10 | | d^5+5d+4=0 | | -3(3p+5)-2(1-11p)=3(7+4p) | | (x+9)18=12/72 | | -7(3+3b)=-6-6b | | (5p-2)-(2p+7)+(-9p+18)= | | 2y+5=-4-4 | | -2(8x+2)=4(x+6.5) | | 8x-7=42 | | (19b-3)-9(2b+3)=-5 |

Equations solver categories